Recombinant Family 1 Carbohydrate-Binding Modules Derived From Fungal Cellulase Enhance Enzymatic Degradation of Lignocellulose as Novel Effective Accessory Protein - Jia, Hexue; Feng, Xiaoting; Huang, Jiamin; Guo, Yingjie; Zhang, Daolei; Li, Xuezhi; Zhao, Jian (Frontiers in Microbiology, 2022)
Fungal cellulases usually contain a family 1 carbohydrate binding module (CBM1), and its role was considered to recognize substrate specifically. This study testified that the CBM1s derived from cellobiohydrolase I of Trichoderma reesei, Penicillium oxalicum, and Penicillium funiculosum could be used as effective accessory protein in cellulase cocktails to enhance the saccharification of lignocellulose, and its enhancement effect was significantly superior to some reported accessory proteins, such as bovine serum albumin (BSA). The promoting effects of the CBM1s were not only related to the CBM1 sources and protein dosages, but also the substrate characteristics and solid consistency during enzymatic hydrolysis. The adsorption capacity of the CBM1s, adsorption kinetic of TrCBM from T. reesei and cellobiohydrolase, endoglucanase and β-glucosidase from P. oxalicum, and the effect of adding TrCBM on enzyme activities of free cellulases in hydrolysis system were investigated, and the binding conformations and affinities of CBM1s to cellulose and lignin were predicted by molecular docking. It was speculated that the higher affinity of the CBM1s to lignin than cellulases could potentially enable the CBM1s to displace cellulase adsorbed on lignin or to preferentially adsorb onto lignin to avoid ineffective adsorption of cellulase onto lignin, which enhanced cellulase system efficiency during enzymatic hydrolysis of lignocellulose.